Development Of Multi-Component Degradable Plastics Through The Combination Of The Sago Starch And Polyethylene/Poly (E-Caprolactone) Blends [TP1180.B55 L732 2007 f rb]. - Lim, Wei Lee (2007)
In this research, sago starch (SS),poly(ε-caprolactone) (PCL) were incorporated into low density polyethylene (LDPE). Poly(ethylene-co-acrylic) acid (EAA) was added into the blend to study the effect on thermo-oxidative ageing (TOA).